2016
DOI: 10.1542/peds.2016-0076
|View full text |Cite
|
Sign up to set email alerts
|

Prepubertal Adiposity, Vitamin D Status, and Insulin Resistance

Abstract: OBJECTIVE: To evaluate the following from prepuberty to the puberty-onset: (1) changes in serum 25-hydroxyvitamin-D (25[OH]D), adiposity, and insulin resistance (IR); (2) the effect of prepubertal adiposity on serum 25(OH)D changes; and (3) the combined effect of prepubertal obesity and suboptimal-25(OH)D on IR at puberty-onset. METHODS:A total of 426 prepubertal children (∼54% girls) were followed during pubertalonset assessing before and after puberty-onset serum 25(OH)D, adiposity (BMI and waist circumferen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 36 publications
2
23
1
3
Order By: Relevance
“…12 This is consistent with the recommendations made by the European Society for Paediatric Gastroenterology, Hepatology and Nutrition (ESPGHAN) to administer VD at 800-1000 IU/day estimated based on feeding and oral supplementation. 13 Obesity and VDD: The evidence obtained from prepubertal children shows a reverse association between 25(OH)D serum levels and adiposity indicators, 14,15 and this is consistent with the hypothesis of VD sequestration in adipose tissue because of its lipid-soluble nature. 16 These findings are also consistent with a recent study that demonstrated that excess weight in children had an effect on VD supplementation and that these children achieved a lower 25(OH) D increase; therefore, children with excess weight may require higher VD doses than normal weight children to achieve the same 25(OH)D levels.…”
Section: Clinical Characteristics Of Vitamin D Deficiency In Childrensupporting
confidence: 74%
See 1 more Smart Citation
“…12 This is consistent with the recommendations made by the European Society for Paediatric Gastroenterology, Hepatology and Nutrition (ESPGHAN) to administer VD at 800-1000 IU/day estimated based on feeding and oral supplementation. 13 Obesity and VDD: The evidence obtained from prepubertal children shows a reverse association between 25(OH)D serum levels and adiposity indicators, 14,15 and this is consistent with the hypothesis of VD sequestration in adipose tissue because of its lipid-soluble nature. 16 These findings are also consistent with a recent study that demonstrated that excess weight in children had an effect on VD supplementation and that these children achieved a lower 25(OH) D increase; therefore, children with excess weight may require higher VD doses than normal weight children to achieve the same 25(OH)D levels.…”
Section: Clinical Characteristics Of Vitamin D Deficiency In Childrensupporting
confidence: 74%
“…Given that few foods contain enough VD to cover vitamin requirements (Table 2) and that food vitamin contents vary depending on cooking methods (e.g., fried fish loses 50% of VD), 53 strategies such as fortified food consumption and the administration of 400 IU/day during the first year of life have proven to be costeffective. 15 Decades ago, oral doses of 600 000 IU were used worldwide to prevent VDD. However, subsequent studies found a higher probable effect on calcium metabolism, height involvement, and increased blood pressure.…”
Section: Vitamin D Deficiency Prevention In Children and Adolescentsmentioning
confidence: 99%
“…When comparing our results of plasma 25(OH) D concentrations with a recent study of 426 healthy school children that live in Santiago, Chile, we found that 39.7% of the sample had suboptimal 25(OH)D values (< 30 ng/ml), which is much less than the 75% observed in our study 29 .…”
Section: Discussioncontrasting
confidence: 49%
“…12 Esta evidencia coincide con la recomendación de la European Society for Paediatric Gastroenterology Hepatology and Nutrition (ESPGHAN), con aportes de 800 a 1000 UI de VD diarios, calculados a partir de alimentación y suplemento oral. 13 Obesidad y DVD: La evidencia en niños prepúberes muestra una relación inversa entre las concentraciones séricas de 25(OH)D e indicadores de adiposidad, 14,15 que es consistente con la hipótesis del secuestro de la VD por el tejido adiposo, dada su naturaleza liposoluble. 16 Además, estos resultados coinciden con un estudio reciente que mostraba que el exceso de peso en niños influía en el suplemento farmacológico de VD y lograba una menor alza de 25(OH)D; por lo tanto, los niños con exceso de peso podrían requerir dosis mayores de VD Enfermedad celíaca Dieta libre de gluten.…”
Section: Clínica De La Deficiencia De Vitamina D En Niños Y Adolescentesunclassified
“…: en la fritura del pescado, se disminuye la VD en un 50%), 53 estrategias como el consumo de alimentos fortificados y la administración de 400 UI/día durante el primer año de vida han probado ser costo-efectivas. 15 Décadas atrás, a nivel mundial, se usaron dosis orales de 600 000 UI para prevenir la DVD. Sin embargo, estudios posteriores encontraron una mayor probabilidad de efectos sobre el metabolismo del calcio, compromiso de talla y aumento de presión arterial.…”
Section: Prevención De La Deficiencia De Vitamina D En Niños Y Adolesunclassified